Pengaruh Perhatian Orang Tua Rantau terhadap Karakter Anak di Desa Parandangan - Ferdyansa Kala’ Allo; Tarcius Sunaryo; Lisa Gracia K (Journal on Education, 2022)
Adolescence is the most vulnerable period, because during that period is a period of transition from childhood to adolescence. At this time, adolescents in a time full of teenage turmoil and high emotional levels. The subject of this research is SMK Negeri 4 Toraja Utara where most of the students have been cared for by their grandmother from a young age. The purpose of making this article is to find out how effective it is both on an emotional level and on a social level with other people in relation to the child's future interactions. It is hoped that this way they can see the condition of the children who have been left behind by their parents, how their character development is, who influences them and how is the family's upbringing.